Analisis Kinerja Keuangan Melalui Pengukuran Likuiditas, Solvabilitas, Dan Profitabilitas ( Studi PT Bank Syariah Indonesia Periode 2021-2023) - Bastian, Bastian Pinoci; Adetio Setiawan, Romi; Putra Ahmad Hasibuan, Rahmat (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study aims to determine the level of health of financial performance at Bank Syariah Indonesia in terms of measuring liquidity, solvability, and profitability ratios. This study is a descriptive study using quantitative methods to analyze financial statements and measure financial performance using liquidity, solvability and profitability measurements at PT Bank Syariah Indonesia for the 2021-2023 period. The results of this study are seen from the liquidity ratio on the Current Ratio, Cash Ratio and Loan to Asset Ratio indicators in a very healthy state, from the Quick Ratio in a healthy state, while from the Loan to Deposit ratio indicator in an unhealthy state. Judging from the solvabilty ratio on the Primary Ratio indicator in a healthy state, the Secondary Risk Ratio in a very healthy state, the Capital Ratio in a fairly healthy state. Judging from the profitability ratio on the Return on Assets and Net Profit Margin indicators in a fairly healthy state, while the Return on Equity indicator in a healthy state.